Mindfulness, empathy and moral sensitivity in nurses: a structural equation modeling analysis - Yasser Rezapour-Mirsaleh; Mahdi Aghabagheri; Azadeh Choobforoushzadeh; Azra Mohammadpanah Ardakan (BMC, 2022)
Abstract Background Ethical issues may pose challenges to nurses; moral sensitivity can help them to overcome these challenges. Identifying variables related to moral sensitivity can help in planning to increase nurses' moral sensitivity. This study aimed to investigate the relationship among mindfulness, empathy, and moral sensitivity in a sample of nurses. Methods In the present study, a cross-sectional design utilizing Structural Equation Modeling (SEM) was conducted. The nurses in a private hospital in Yazd, Iran, were invited to participate in the study (n=162) using simple random sampling. In order to gather the data, the Freiburg's mindfulness inventory, moral sensitivity questionnaire, and revised Jefferson's empathy scale were used. The hypothesized model was analyzed by SEM. Results The results show that Mindfulness (β=0.41, t=5.53, p<0.01) and empathy (β=0.52, t=6.77, p<0.01) had a significant direct effect on moral sensitivity. However, mindfulness had an indirect effect on nurses' moral sensitivity via empathy improvement (z= 6.25, p<.01). Conclusion Empathy played a significant mediating role in the relationship between mindfulness and moral sensitivity, so mindfulness-based interventions with an emphasis on empathy may provide an opportunity to increase moral sensitivity in nurses.